STUDIES ON IRRIGATION AND WEED MANAGEMENT FOR ENHANCING RICE YIELD AND WATER PRODUCTIVITY UNDER SYSTEM OF RICE INTENSIFICATION - RAJAN KUMAR,; SHIVNATH DAS,; VINOD KUMAR,; 1, D. K. DWIVEDI,; LIPIKA DAS, (The Bioscan, 2015)
Plant height (113.68 cm),LAI (3.04),crop growth rate(11.96 g/day/m2) number of panicles/m2, (249.23) grain weight/panicle, (3.62 gm) grain and straw yield (64.07 q/ha) (86.85q/ha) respectively were found to be maximum under the treatment continuous submergence to 2.5 cm and were showed significantly superior over submergence to 2.5 cm 5 DAD but statisticallyat par with 1 DAD and 3 DAD.Higher water use efficiency (82.99kg/ha-cm) and water productivity (6.87 Rs/m3) were found with submergence to 2.5 cm 3 DAD. Similarly levels of mechanical weedings has significant influenced on growth and yield attributes,grainand straw yield (64.18q/ha) (85.83q/ha) respectively. These were found maximum with the rotary weeding at 10, 20, 30 and 40 DAT which was significantly superior over rotary weeding at 20 and 40 DAT but statistically were at par with rotary weeding at 20, 30 and 40 DAT. Test weight was not affected significantly due to irrigation and mechanical weeding treatments. Thus Irrigation of 2.5 cm water at 3 DAD and rotary weeding at 20, 30 and 40 days after transplanting should be practiced for getting higher grain yield, water use efficiency and water productivity of rice under SRI in agro-climatic zone 1 of Bihar.